Supportive leadership and employee creativity: Will Leader-Member Exchange (LMX) mediate the relationship? - Prinhandaka, Dwinanda Jalu Prasetya; Rohman, Isnanda Zainur; Wijaya, Nikodemus Hans Setiadi (goodwood publishing, 2022)
Purpose: This study proposes to integrate supportive leadership, Leader-Member Exchange (LMX), and employee creativity. It suggests that LMX can mediate this relationship. Research Methodology: A total of 200 participants were included in this study. They worked for a tobacco company located in a district in Kulon Progo, Yogyakarta, Indonesia. Analysis for hypotheses was done in SPSS and AMOS. Results: Supportive leadership was positively related to LMX and employee creativity. LMX was positively related to employee creativity. Finally, LMX mediates the relationship between supportive leadership and employee creativity. Conclusions: This study found that supportive leadership positively impacts both LMX and employee creativity, with LMX mediating the relationship between the two. This emphasizes the importance of supportive leadership in fostering strong LMX relationships, which enhances employee creativity. However, the study's limitations, such as the use of a single-company sample and cross-sectional data, suggest that further research with broader samples and multi-wave data collection is needed to validate these findings. Limitations: The participants in this study came from only one company. This might lower the generalizability of the results. Another limitation of this study is the use of a cross-sectional method in data collection, which might result in common method variance. Future studies could employ other data collection methods. For example, a multi-wave data collection can remedy this problem. Contributions: This study suggests that a supportive leadership style is necessary for implementation because it can promote a higher quality of the relationship between employees and their supervisors. More importantly, this aligns with organizational efforts to foster employee creativity.